Réponses

2013-09-15T10:17:29+02:00
a)3(x+4)                b)(x-4)-(2+4x)               c)4-(xpuissance2+5x-8)           d)(x+2)(x+6)

a = 3x+12
b = x-4-2-4x = -3x -6
c= 4 -(x²+5x-8) = 4-x²-5x+8 = -x² -5x +12
d = x²+6x +2x +12 = x² + 8x +12
2013-09-15T10:19:00+02:00
A) = 3(x+4)
= 3*x + 3*4
=3x + 12

b) = (x-4)-(2+4x)
=x*2 + x*4x - 4*2 + 4*4x
= 2x + 4x^{2} - 8 + 16x
= 18x +  4x^{2} - 8

c) =4( x^{2} +5x - 8
=4 -  x^{2} + 5x - 8
=12 -  x^{2} + 5x

d) =(x+2)(x+6)
= x*x+x*6*2*x+2*6
= x^{2} + 6x * 2x + 12
= x^{2} + 12x + 12